Process and impact of mergers of NHS trusts: multicentre case study and management cost analysis. Issue 7358 (3rd August 2002) - Fulop, Naomi; Protopsaltis, Gerasimos; Hutchings, Andrew; King, Annette; Allen, Pauline; Normand, Charles; Walters, Rhiannon
Abstract: Objective : To study the processes involved in and impact of mergers between NHS trusts, including the effect on management costs. Design : Cross sectional study involving in depth interviews and documentary analysis; case study to compare savings in management costs between case trusts and control trusts. Setting : Nine trusts (cross sectional study) and four trusts (case study) in London. Participants : 96 interviews with trust board members, other senior managers, clinicians, service managers, and representatives of health authorities, regional office, community health councils, local authorities, other trusts in the area, and primary care groups and trusts. Main outcome measures : Stated and unstated drivers, and impact of merger on delivery and development of services, management structures, and staff recruitment, retention, and morale. Effects of difference in trust size before and after the merger. Savings in management costs two years after merger. Results : Some important drivers for merger are not publicly stated. Mergers had a negative effect on delivery of services because of a loss of managerial focus on services. Planned developments in services were delayed by at least 18 months. Trusts' larger sizes after mergers had unintended negative consequences, as well as predicted advantages. The tendency for one trust's management team to dominate over the other resulted in tension. No improvement in recruitment or retention of clinical and managerial staff was reported. Perceived differences in organisational culture were an important barrier to bringing together two or more organisations. Two years after merger, merged trusts had not achieved the objective of saving £500 000 a year in management costs. Conclusions : Important unintended consequences need to be accounted for when mergers are planned. Mergers can cause considerable disruptions to services, and require greater management support than previously acknowledged. Other organisations undergoing restructuring, such as primary care groups developing into primary care trusts and health authorities merging into strategic health authorities, should take these findings into account.